2020
DOI: 10.3390/insects11070410
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Vegetation Characteristics Drive Insect Ensemble Structures in a Desert Ecosystem: The Tenebrionid Beetles (Coleoptera: Tenebrionidae) Inhabiting the Ulan Buh Desert (Inner Mongolia, China)

Abstract: In community ecology, ensembles are defined as phylogenetically bounded groups of species that use a similar set of resources within a community. Tenebrionids are a conspicuous faunal component of Asian deserts, but little is known about their community ecology. We investigated if tenebrionids associated with different plant species constitute ensembles with a different ecological structure. Sampling was done with pitfall traps placed beneath the most common plant species. Tenebrionid abundance pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In our case, rarefaction applied to the steppe level appeared justified, because of the different sampling effort (sampling effort in the typical and meadow steppes was two and three times that of the desert steppe). With the use of rarefaction, both Fisher's α-values and θ-values increased in the order: desert steppe < typical steppe < meadow steppe, which indicates an increasing diversity from the most to the least arid type of steppe, which can be in turn related to the increasing vegetation cover, as it seems that communities of ground-dwelling arthropod predators and detritivores are mainly determined by vegetation cover and aboveground plant biomass (Pan et al, 2018;Niu et al, 2020). These results are also consistent with our findings in a previous study (Tsafack et al, 2020), where the desert steppe showed lower Brillouin and Shannon-Wiener diversity indices, while typical and meadow steppes showed equally higher species diversity values; the species richness indices Chao and Margalef showed the same results, increasing in the order: desert steppe < typical steppe < meadow steppe.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, rarefaction applied to the steppe level appeared justified, because of the different sampling effort (sampling effort in the typical and meadow steppes was two and three times that of the desert steppe). With the use of rarefaction, both Fisher's α-values and θ-values increased in the order: desert steppe < typical steppe < meadow steppe, which indicates an increasing diversity from the most to the least arid type of steppe, which can be in turn related to the increasing vegetation cover, as it seems that communities of ground-dwelling arthropod predators and detritivores are mainly determined by vegetation cover and aboveground plant biomass (Pan et al, 2018;Niu et al, 2020). These results are also consistent with our findings in a previous study (Tsafack et al, 2020), where the desert steppe showed lower Brillouin and Shannon-Wiener diversity indices, while typical and meadow steppes showed equally higher species diversity values; the species richness indices Chao and Margalef showed the same results, increasing in the order: desert steppe < typical steppe < meadow steppe.…”
Section: Discussionmentioning
confidence: 99%
“…The climate is characterized by sufficient sunshine, little rain, hot summers, cold winters, large daily temperature differences, strong evaporation, strong winds, and a short frost-free period. The average annual temperature reaches 8.6 • C. The highest temperature in July is 38.7 • C, the lowest temperature in January is −32.8 • C, the average annual precipitation reaches 116-162 mm, and the average annual evaporation is 2560-3200 mm [45,46]. The main vegetation is sea buckthorn, sand holly, white thorn, overlord, red yarn, and reed.…”
Section: Study Areamentioning
confidence: 99%
“…The average annual temperature reaches 8.6 °C. The highest temperature in July is 38.7 °C, the lowest temperature in January is −32.8 °C, the average annual precipitation reaches 116-162 mm, and the average annual evaporation is 2560-3200 mm [45,46]. The main vegetation is sea buckthorn, sand holly, white thorn, overlord, red yarn, and reed.…”
Section: Study Areamentioning
confidence: 99%
“…Arthropods, the main component of global biodiversity, are declining in abundance and biodiversity in many regions of the world [1,2] and they are still a very unknown group. In this new geological epoch, called the Anthropocene [3], or Homogenocene [4,5], arthropods continue to be the "hidden biodiversity" not only in the tropics [6,7], but also in subtropical arid environments that have been traditionally overlooked by conservation efforts [8,9]. Similarly, there are still huge information and knowledge gaps regarding the biodiversity of arthropods in desert ecosystems (i.e., Linnean, Wallacean, and Prestonian shortfalls) [10,11].…”
Section: Introductionmentioning
confidence: 99%